2016
DOI: 10.1016/j.ijhydene.2016.09.125
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility analysis of a novel solid-state H2 storage reactor concept based on thermochemical heat storage: MgH2 and Mg(OH)2 as reference materials

Abstract: This paper discusses the feasibility of a novel adiabatic magnesium hydride (MgH2) reactor concept based on thermochemical heat storage. In such a concept, the heat of reaction released during the absorption of hydrogen is stored by a thermochemical material in order to be reused in a subsequent desorption stage. Magnesium hydroxide (Mg(OH)2) has been selected as the suitable material for integration into the MgH2 storage system due to its thermodynamic properties. An analytical formulation of hydrogen absorpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 36 publications
(71 reference statements)
0
14
0
Order By: Relevance
“…Although the complexity of the MgH2 tank was simplified with the use of PCM to store and recover the heat of reaction, the gravimetric capacity of the system was found to be 0.315 wt.% versus 6 wt.% for the MgH2 + 5 wt.% ENG (expanded natural graphite) pellets incorporated into the storage tank, due to the weight of the PCM [13]. In a recent publication [17], the feasibility of an adiabatic MgH2 reactor based on thermochemical heat storage has been discussed; and preliminary analytical results have shown that the combination of MgH2 with magnesium hydroxide (Mg(OH)2) can lead to a competitive hydrogen absorption time compared to the MgH2-PCM reactor, while reducing the mass of the heat storage media by a factor of 4, using an inexpensive thermochemical heat storage material with a higher energy density compared to the metallic PCM, and operating at more flexible pressure and temperature conditions.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although the complexity of the MgH2 tank was simplified with the use of PCM to store and recover the heat of reaction, the gravimetric capacity of the system was found to be 0.315 wt.% versus 6 wt.% for the MgH2 + 5 wt.% ENG (expanded natural graphite) pellets incorporated into the storage tank, due to the weight of the PCM [13]. In a recent publication [17], the feasibility of an adiabatic MgH2 reactor based on thermochemical heat storage has been discussed; and preliminary analytical results have shown that the combination of MgH2 with magnesium hydroxide (Mg(OH)2) can lead to a competitive hydrogen absorption time compared to the MgH2-PCM reactor, while reducing the mass of the heat storage media by a factor of 4, using an inexpensive thermochemical heat storage material with a higher energy density compared to the metallic PCM, and operating at more flexible pressure and temperature conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The two described operating modes are governed by different conditions of temperature and pressure to be imposed to the hydrogen and thermochemical heat storage media as discussed in Ref. [17].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations